2021
DOI: 10.1177/0972262920977986
|View full text |Cite
|
Sign up to set email alerts
|

How Green Consumption Value Affects Green Consumer Behaviour: The Mediating Role of Consumer Attitudes Towards Sustainable Food Logistics Practices

Abstract: The aim of the study is to identify the green consumption values and production patterns and understand how they impact consumer behaviour and purchase intention of green consumers, in particular, the environment-conscious youth in the city of Bangalore. The focus of the study is on the pre-purchase sustainable logistics of food products and how they impact behaviour and attitudes of green consumers. The theory of planned behaviour and social cognitive theory form the theoretical base for the current research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 70 publications
2
6
0
2
Order By: Relevance
“…The impacts of three antecedents on the TPB on purchase intention regarding green products have empirically been confirmed by previous studies (Alagarsamy et al , 2021; Emekci, 2019; Xu et al , 2020). Nevertheless, the impact magnitudes of three components from the TPB on green purchase intention were not consistent and dependent on the particular context of each research (Nguyen, 2019) while there is a lack of studies considering the effects of subjective norms on attitude towards green products and perceived behavioral control.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 76%
See 2 more Smart Citations
“…The impacts of three antecedents on the TPB on purchase intention regarding green products have empirically been confirmed by previous studies (Alagarsamy et al , 2021; Emekci, 2019; Xu et al , 2020). Nevertheless, the impact magnitudes of three components from the TPB on green purchase intention were not consistent and dependent on the particular context of each research (Nguyen, 2019) while there is a lack of studies considering the effects of subjective norms on attitude towards green products and perceived behavioral control.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 76%
“…In the present study, therefore, we re-test the associations between three precursors and green purchase intention among Vietnamese consumers. Also, some recent studies suggested that subjective norms can stimulate or restrain consumers' attitude towards green products and perceived behavior control (Paul et al, 2016;Shukla, 2019) as judgment on whether buying environmentally friendly products is good or bad and the perception of ease or difficulty of buying green products can be affected by consumers' perceived societal pressures to engage in buying green products (Alagarsamy et al, 2021;Nguyen et al, 2018). Besides, personal judgments of an individual's capacities to carry out a specific action can be positively associated with the attitude towards this behavior (Cristea and Gheorghiu, 2016;Doanh, 2021).…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The study positively verified hypotheses H3a and H3b, meaning that there is a relationship between the GCV scale and savings behaviours inside (β = 0.204) and outside the home (β = 0.260). These results are consistent with previous studies on Polish society conducted by Bartoszczuk, Singh and Rutkowska [34] and Alagarsamy, Mehrolia and Mathew [60]. Interestingly, pro-environmental attitudes more strongly determine respondents to motivate others to save energy than to save energy in their immediate environment.…”
Section: Discussionsupporting
confidence: 91%
“…Food industry [20] 2021 Survey on Indian young consumer green values impact on green behaviour towards green food logistics.…”
Section: Reference Year Studymentioning
confidence: 99%